SEMANTIC STUDY OF IDIOMATIC EXPRESSIONS IN TAYLOR SWIFT’S “DANCING WITH OUR HANDS TIED” LYRICS - Amanah, Firma Pradesta; Pitaloka, Nova Lingga; Lianasari (Jurnal Ilmiah Bina Bahasa, 2025)
Idiomatic expressions are an essential component of language, often used in literature and music to convey complex emotions and abstract ideas. In the realm of contemporary music, particularly pop lyrics, idioms play a crucial role in enhancing expressive depth. However, there remains limited research on how idioms function within modern song lyrics. This study aims to analyze the use of idiomatic expressions in Taylor Swift’s song “Dancing with Our Hands Tied” to explore how figurative language contributes to lyrical meaning. Addressing this gap, the research employs a qualitative method, collecting data through close observation, including repeated listening and textual analysis of the lyrics. The idioms identified were analyzed using Seidl and McMordie’s classification framework. The findings reveal 22 idiomatic expressions categorized into nine types, including key words with idiomatic uses, idioms with nouns and adjectives, idiomatic pairs, idioms with prepositions, phrasal verbs, verbal idioms, idioms with special subjects, idioms with key words from specific categories, and idioms with comparison. These idioms are shown to reflect emotional tension, love, and inner conflict. The findings suggest that Taylor Swift effectively employs idiomatic language to convey the emotional complexities and nuanced experiences associated with love, thereby enhancing the expressive power of her lyrics.